Troublesome Construction: The Rationale and Risks of IIRSA - Pitou van Dijck (European Review of Latin American and Caribbean Studies, 2008)
Latin American countries are involved in implementing a continental-wide infrastructure programme to deepen regional integration and facilitate their insertion in international markets. The IIRSA [Iniciativa para la Integración de la Infraestructura Regional Suramericana] program- me includes ten so called development hubs that may contribute to significant change in the location of economic activities in the continent as well. They may as well have a substantial impact on the environment in regions adjacent to the corridors. This study deals with the rationale and organization of the IIRSA infrastructure programme. Subsequently the study focuses on the spatial impact such corridors may have and the environmental, social and economic implication of these roads. Finally the paper deals with some critical methodological problems involved in the making of of strategic environmental assessment studies of IIRSA-related road infrastructure projects.  Resumen: Una construcción problemática: Razones y riesgos de IIRSALos países latinoamericanos están implementando un programa continental de infraestructura para profundizar la integración regional y facilitar su inserción en los mercados internacionales. El programa de IIRSA [Iniciativa para la Integración de la Infraestructura Regional Surameri cana] incluye diez centros de desarrollo que pueden contribuir a cambios importantes en la ubicación de las actividades económicas en el continente. Estos centros podrían tener un impacto substancial en el medioambiente de las regiones adyacentes a los corredores. Este estudio se ocupa de las razones y organización del programa de infraestructura de IIRSA. Luego nos concentramos en el impacto espacial que pueden tener esos corredores y las implicaciones sociales, económicas y para el medioambiente de esos caminos. Finalmente tratamos en el artículo algunos críticos problemas metodológicos en la elaboración de evaluaciones medioambientales estratégicas de proyectos de infraestructura vial de IIRSA.